2017
DOI: 10.1128/msystems.00050-17
|View full text |Cite
|
Sign up to set email alerts
|

Parasite Microbiome Project: Systematic Investigation of Microbiome Dynamics within and across Parasite-Host Interactions

Abstract: Understanding how microbiomes affect host resistance, parasite virulence, and parasite-associated diseases requires a collaborative effort between parasitologists, microbial ecologists, virologists, and immunologists. We hereby propose the Parasite Microbiome Project to bring together researchers with complementary expertise and to study the role of microbes in host-parasite interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 22 publications
(22 reference statements)
0
38
0
1
Order By: Relevance
“…Although the term "microbiome" is often used in reference to any type of sequencing-based assessment of microbial biodiversity [e.g., the Earth Microbiome Project (Gilbert, Jansson, & Knight, 2014) or the troposphere microbiome (DeLeon-Rodriguez et al, 2013)], the term is most commonly used to define any species found in association with a specific host organism, including known bacterial symbionts [(endo-or ectosymbionts such as Wolbachia or sulphurutilizing bacteria (Ainsworth et al, 2015;Nicks & Rahn-Lee, 2017;Sayavedra et al, 2015;Werren, 1997)] specialized microbial populations that are adapted to life in host-associated habitats such as mucus, gut linings or skin (Glasl, Herndl, & Frade, 2016;Larsen, Bullard, Womble, & Arias, 2015;Schommer & Gallo, 2013;Walke et al, 2017;Walter & Ley, 2011;Weese, 2013), and partially digested gut contents and prey items that can be identified via DNA sequencing (De Barba et al, 2014;Deagle, Kirkwood, & Jarman, 2009;Yu et al, 2012;Zeale, Butlin, Barker, Lees, & Jones, 2011). Common microbiome taxa include both parasitic and commensal species (Dheilly et al, 2017;Nunes-Alves, 2015;Parfrey et al, 2011;Schommer & Gallo, 2013), with host-associated species spanning both prokaryotic and eukaryotic domains of life.…”
Section: Introductionmentioning
confidence: 99%
“…Although the term "microbiome" is often used in reference to any type of sequencing-based assessment of microbial biodiversity [e.g., the Earth Microbiome Project (Gilbert, Jansson, & Knight, 2014) or the troposphere microbiome (DeLeon-Rodriguez et al, 2013)], the term is most commonly used to define any species found in association with a specific host organism, including known bacterial symbionts [(endo-or ectosymbionts such as Wolbachia or sulphurutilizing bacteria (Ainsworth et al, 2015;Nicks & Rahn-Lee, 2017;Sayavedra et al, 2015;Werren, 1997)] specialized microbial populations that are adapted to life in host-associated habitats such as mucus, gut linings or skin (Glasl, Herndl, & Frade, 2016;Larsen, Bullard, Womble, & Arias, 2015;Schommer & Gallo, 2013;Walke et al, 2017;Walter & Ley, 2011;Weese, 2013), and partially digested gut contents and prey items that can be identified via DNA sequencing (De Barba et al, 2014;Deagle, Kirkwood, & Jarman, 2009;Yu et al, 2012;Zeale, Butlin, Barker, Lees, & Jones, 2011). Common microbiome taxa include both parasitic and commensal species (Dheilly et al, 2017;Nunes-Alves, 2015;Parfrey et al, 2011;Schommer & Gallo, 2013), with host-associated species spanning both prokaryotic and eukaryotic domains of life.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of microorganisms as vectors of other microbes or viruses into the holobiome should not be overlooked, given, for example, the role of the protistan root parasite Polymyxa in transmitting a range of pathogenic viruses into crop plants [45]. The pathogenic and functional consequences of hyperparasitic associations have not received much attention (but see, for example, [46]), compounded by the fact that the extent of microbial hyperparasitism is likely underestimated (e.g., [47,48]).…”
Section: Trends In Ecology and Evolutionmentioning
confidence: 99%
“…The parasitology field is beginning to recognize that parasite-associated microbes, including viruses, can affect parasite fitness and influence the outcome of parasitic infection, and these microbes may be targeted for treatment of parasitic diseases [11][12][13][14][15]. We need to characterize the virome of parasitic organisms to understand the role of parasites in virus evolution and host-microbe interactions, to determine the role of viruses in parasite virulence, and to identify patterns and processes of host-parasite-virus coevolution [14].…”
Section: Introductionmentioning
confidence: 99%